Eco-Theology - Deane-Drummond, Celia (2008)
Concern for the environment has developed and intensified over the last few decades to the point where it now dominates much of our contemporary political landscape and culture. The rise of religious environmentalism in particular adds its own distinctive voice to the debate, for it seeks to trace both the malaise and a potential solution to environmental understanding. In Eco-Theology, Celia Deane-Drummond offers a comprehensive resource book for this burgeoning field of enquiry that highlights and seeks to evaluate the merits or otherwise of contemporary eco-theologies. She introduces the reader to critical debates in eco-theology, tracing trends from around the globe and key theological responses, and encourages reflection and analysis through further reading sections at the end of each chapter and questions for discussion.